2023
DOI: 10.3390/app13095295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rainfall Intensity and Slope on the Slope Erosion of Longling Completely Weathered Granite

Abstract: Serious slope erosion occurs in the distribution areas of fully weathered granites, and rainfall intensity and slope gradient are important factors affecting slope erosion. In this study, we investigate the erosion characteristics of Longling completely weather granites with a focus on the effects of rainfall intensity and slope gradient. Based on an indoor 60-min simulated rainfall test, we selected four slope gradients (10°, 20°, 30°, and 40°) and three rainfall intensities (50, 80, and 110 mm/h) for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Gao Anqi et al [18] obtained the surface deformation rule of a slope-affected area through a detailed investigation of buildings in the urban area around the Fushun West Open-Pit Mine, a comprehensive analysis of urban geological conditions, surface monitoring data, and numerical simulation. Based on the indoor 60 min simulated rainfall test, Tian, H. [19] found that the rainfall intensity and slope are two key factors that determine slope velocity and summarized the functional relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…Gao Anqi et al [18] obtained the surface deformation rule of a slope-affected area through a detailed investigation of buildings in the urban area around the Fushun West Open-Pit Mine, a comprehensive analysis of urban geological conditions, surface monitoring data, and numerical simulation. Based on the indoor 60 min simulated rainfall test, Tian, H. [19] found that the rainfall intensity and slope are two key factors that determine slope velocity and summarized the functional relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…In the actual process of erosion, the simultaneous influence of various factors makes the soil erosion process complex. Previous research has demonstrated that artificially simulated rainfall experiments are an effective method for investigating soil erosion processes and their influencing factors [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from herbs, slope gradient and flow discharge were identified as important factors influencing the hydraulic characteristics of slope runoff. Tian et al conducted artificial rainfall experiments and concluded that slope gradient is a key determinant of slope flow velocity (Tian and Kong, 2023). Huang et al suggested that higher slope gradients result in greater water flow energy and surface velocity (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%